Crimes of terror: the legal and political implications of federal terrorism prosecutions - Said, Wadie E. (Oxford Univ. Press, 2015)
Informants, spies, radicalization, and entrapment -- The continual evolution of the material support ban -- Evidence and the criminal terrorist prosecution -- The implications and broad horizons of the terrorism prosecution -- The final stop : sentencing and confinement